2017
DOI: 10.21037/atm.2017.07.08
|View full text |Cite
|
Sign up to set email alerts
|

Driving pressure and mechanical power: new targets for VILI prevention

Abstract: Several factors have been recognized as possible triggers of ventilator-induced lung injury (VILI).The first is pressure (thus the 'barotrauma'), then the volume (hence the 'volutrauma'), finally the cyclic opening-closing of the lung units ('atelectrauma'). Less attention has been paid to the respiratory rate and the flow, although both theoretical considerations and experimental evidence attribute them a significant role in the generation of VILI. The initial injury to the lung parenchyma is necessarily mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0
20

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(174 citation statements)
references
References 40 publications
3
139
0
20
Order By: Relevance
“…Mechanical ventilation plays a key role in the treatment of patients with ARDS, although it may cause ventilator-induced lung injury (VILI) [2]. In recent years, it has been found that, during mechanical ventilation of ARDS patients, mechanical power (MP) can be used to evaluate and prevent VILI compared to other mechanical parameters, such as driving pressure, transpulmonary pressure (Ptp), respiratory rate (RR), and positive end-expiratory pressure (PEEP) [3]. It indicates the energy that the ventilator delivers to the entire respiratory system in one minute, expressed as J/min.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical ventilation plays a key role in the treatment of patients with ARDS, although it may cause ventilator-induced lung injury (VILI) [2]. In recent years, it has been found that, during mechanical ventilation of ARDS patients, mechanical power (MP) can be used to evaluate and prevent VILI compared to other mechanical parameters, such as driving pressure, transpulmonary pressure (Ptp), respiratory rate (RR), and positive end-expiratory pressure (PEEP) [3]. It indicates the energy that the ventilator delivers to the entire respiratory system in one minute, expressed as J/min.…”
Section: Introductionmentioning
confidence: 99%
“…• En caso de usar VMNI, utilizar PEEP altas y presiones de soporte bajas (con el objetivo de obtener un VTe < 9 ml/kg de peso ideal) 31,32 .…”
Section: Criterios Gasométricosunclassified
“…To explain this complicated process in more simple terms: the inspiratory flow conveys a given tidal volume based on the pressure delivered in a unit of time, which is, in turn, determined by the respiratory rate and the I:E ratio (inspiration:expiration ratio). The higher the respiratory rate, the lower the inspiratory time and the higher the flow, resulting in greater pressure applied to the lung parenchyma and an increased risk of VILI [47].…”
Section: Benefits Risksmentioning
confidence: 99%